The Concept of Islamic Education from the Perspective of Ontology, Epistemology, and Axiology - Alihan Satra; Ezarryal Radditya; Rendy Hernawan (Advances In Education Journal, 2025)
In a culture where changes in human behavior are challenged by the advancement of the times, education is essential.  Therefore, we require new, comprehensive formulations of the idea of education, particularly Islamic education, which is the subject of this study.  This study aims to explain Islamic educational philosophy's ontology, epistemology, and axiology. When gathering data, a qualitative approach using literature study approaches is used, followed by descriptive analysis and a conclusion to address the problem.  The study's findings demonstrate that ontology encompasses examination, criticism, correction, and foundation. On the other hand, sources, methods, techniques, and objects are all part of epistemology. The ideals of worship, ihsan, future, mercy, trust, da'wah, and tabsyir are part of the axiology of Islamic educational philosophy.